The Importance of Digital Campaigns for Students: Critical Solutions to Ecosystem Change for Fostering Environmental Awareness in Ecology Courses - Rizqi (Universitas Cokroaminoto Palopo, 2026)
The accelerating changes in ecosystems caused by human activities, such as deforestation, urbanisation, pollution, and climate change, demand a critical response from various groups, including students as agents of change. This article examines the importance of digital campaigns as a strategic tool for students to critique ecosystem changes while cultivating environmental awareness. With an analytical critical approach as a lecturer, this article synthesises various research findings and scientific articles that show that digital campaigns not only function as a medium for disseminating information but also as a vehicle for transformative learning that can build ecological awareness, critical thinking skills, and social engagement among students. Digital campaigns are considered relevant to the characteristics of today's student generation, which is closely connected to digital technology and social media.